Language style in Korean beverage advertising slogans - Nur Syafitri; Yulianeta Yulianeta (Universitas Pendidikan Indonesia (UPI), 2021)
Language style is a domain of semantics, used to explore the meaning conveyed by the writers to attract viewers to the texts. Nevertheless, efforts to delve into the manifestation of language style in advertising genre are still not extensively done. This study identifies and describes the types of language style along with its function and meaning, contained in the Korean beverage advertising slogans. The data of this research were the slogans of Korean beverage advertisements that aired in 2019 through YouTube. A descriptive qualitative method was employed by collecting and recording the data. The process continued with the identification of the types language style along with its function and meaning. Finally, the analyzed data were elaborated descriptively. The results revealed that from 30 Korean beverage advertising slogans, 건조체 (geonjoche) was the most frequently occurred style because the simple writing style was only expressed without modifiers with clear sentences. It gave an objective impression that focused on conveying meaning. The affective meaning was the most common meaning found as it related to the listeners or readers’ reaction to the use of words or sentences in the slogans. Furthermore, referential function was found to be the most common one of the language styles identified in the slogans. The reason for this is that the advertising slogans are centered on and used to inform the products. Therefore, such function can persuade the viewers to buy and use the advertised products.